Sheltered but Unsettled: Understanding the Lived Experiences of Homeless Adult Men in Temporary Tent Shelters in Durban, South Africa - Tseole, Nkeka; Pillay, Julian David (Southern African Journal of Social Work and Social Development, 2025)
Homelessness continues to be a pressing global health concern, intensifying vulnerability and health risks among people experiencing the phenomenon. Through in-depth storytelling sessions with ten homeless adult men, this qualitative study explored the lived experiences of homeless men residing in temporary tent shelters in Durban, South Africa. Thematic analysis revealed rich, personal accounts of the men’s experiences. Findings revealed a complex situation of resilience and vulnerability, with five key themes emerging: supportive brotherhood, increased health risks, difficulties with shelter maintenance, compromised privacy, and theft of personal belongings. This study highlights the urgent need for targeted interventions addressing shelter conditions, health services, and security measures in temporary homeless shelters. Interested stakeholders need to prioritise creating dignified, safe, and supportive environments that holistically address the needs of individuals experiencing homelessness.